Cross-Link Structure Affects Replication-Independent DNA Interstrand Cross-Link Repair in Mammalian Cells - Hlavin, Erica M. (2010)
DNA interstrand cross-links (ICLs) are cytotoxic products of common anti-cancer drugs and cellular metabolic processes, whose mechanism(s) of repair remain poorly understood. In this study, we show that cross-link structure affects ICL repair in non-replicating reporter plasmids that contain a mispaired N(4)C-ethyl-N(4)C (C-C), N3T-ethyl-N3T (T-T), or N1I-ethyl-N3T (I-T) ICL. The T-T and I-T cross-links obstruct the hydrogen bond face of the base and mimic the N1G-ethyl-N3C ICL created by bis-chloroethylnitrosourea, whereas the C-C cross-link does not interfere with base pair formation. Host-cell reactivation (HCR) assays in human and hamster cells showed that repair of these ICLs primarily involves the transcription-coupled nucleotide excision repair (TC-NER) pathway. Repair of the C-C ICL was five-fold more efficient than repair of the T-T or I-T ICLs, suggesting the latter’s cross-links hinder lesion bypass following initial ICL unhooking. Luciferase expression from plasmids containing a C-C crosslink remnant on either the transcribed or non-transcribed strand increased in NER-deficient cells, indicating NER involvement occurs at a step prior to remnant removal, whereas expression from similar T-T remnant plasmids was inhibited in NER-deficient cells, demonstrating NER is required for remnant removal. Sequence analysis on repaired plasmids showed a high proportion of Cs inserted at the site of the T-T and I-T cross-links and HCR assays showed that Rev1 was likely responsible for these insertions. In contrast, both Cs and Gs were inserted at the C-C cross-link site and Rev1 was not required for repair, suggesting replicative or other translesion polymerases can bypass the C-C remnant.